Design and development of dual mode on-board battery charger for electric vehicle - Hemalatha Jeekanahalli Nanjappa; Sunanda Channaiah (Institute of Advanced Engineering and Science, 2023)
In recent days there is growing interest in electric vehicle (EVs) technologies because of concern about global warming, energy crisis and security. Charging configurations of EVs play a vital role in the development of automobile transformation. Hence in an automobile industry increased demand of EVs require an efficient and reliable system for recharging the battery. This paper presents a topology that interface the two types of charging systems i.e. slow charging and fast charging as required by the user. TESLA S60 battery model is taken as an example for validation of the proposed topology in simulation. Cuk converter is designed and implemented for charging the battery in two modes. The MATLAB/Simulink software is used to simulate and analyze the performance of the system. The prototype hardware model of the charger is developed and results are validated with simulation. The results show that the slow charging 86% and fast charging efficiency is more than 82%.